Soluble CD14, CD163, and CD27 biomarkers distinguish ART-suppressed youth living with HIV from healthy controls. Issue 4 (29th January 2018) - Williams, Julie C; Zhang, Xinrui; Karki, Manju; Chi, Yueh-Yun; Wallet, Shannon M; Rudy, Bret J; Nichols, Sharon L; Goodenow, Maureen M; Sleasman, John W
Abstract: Objective: To define inflammatory pathways in youth living with HIV infection (YLWH), assessments of biomarkers associated with lymphocyte and macrophage activation, vascular injury, or bone metabolism were performed in YLWH in comparison with healthy controls (HC). Design: Longitudinal multicenter study comparing biomarkers in YLWH suppressed on antiretroviral therapy (ART), those with ongoing viral replication, and HC were compared using single blood samples obtained at end of study. Methods: Twenty-three plasma proteins were measured by ELISA or multiplex assays. Principal component analysis (PCA) was used to define contributions of individual biomarkers to define outcome groups. Results: The study cohort included 129 predominantly African American, male participants, 21–25 years old at entry. Nine biomarkers of lymphocyte and macrophage activation and cardiovascular injury differed between HC and YLWH. Significant positive correlations were identified between lymphocyte and macrophage activation biomarkers among HC and YLWH. Correlations distinct to YLWH were predominantly between biomarkers of macrophage and vascular inflammation. PCA of outcome groups showed HC and suppressed YLWH clustering together for lymphocyte activation biomarkers, whereas macrophage activation markers showed all YLWH clustering distinct from HC. Cardiovascular biomarkers were indistinguishable across groups. Averaged variable importance projection to assess single biomarkers that maximally contribute to discriminate among outcome groups identified soluble CD27, CD14, and CD163 as the 3 most important with TNFα and LPS also highly relevant in providing separation. Conclusions: Soluble inflammatory and lymphocyte biomarkers sufficiently distinguish YLWH from HC. Persistent macrophage activation biomarkers may provide a means to monitor consequences of HIV infection in fully suppressed YLWH.